"Being the master in one’s own house:" Opinions and experiences with the Finnmark Estate - Broderstad, Else Grete; Hausner, Vera Helene; Josefsen, Eva; Søreng, Siri Ulfsdatter (2015)
A part of the panel: "Comparative Perspectives on Self-Determination: Institutional Models and Political Challenges" at the ECPR General Conference Université de Montréal 26-29 August 2015. In northernmost Norway the right to own and manage the land in Finnmark, was transferred from the state to the the Finnmark Estate (FeFo) in 2005. The land tenure arrangement was a result of land claims made by the indigenous Sami people of Norway. The resources and the land that was previously managed to the best for all Norwegian citizens by the state, is now managed to the best for the inhabitants of Finnmark. Based on three surveys in Finnmark, this paper explores the support of people living in Finnmark to the new land tenure arrangements. We used the term diffuse support to describe the acknowledgement by inhabitants of an institution’s ideas, values and principles, while specific support reflects the experiences and support to the operationalization of the principles and goals and the management tasks carried out by an institution. We find that FeFo as an institution has low diffuse support. On the other hand, experiences with FeFo show a clear specific support to the principles, goals and management actions implemented by the estate. In this article, we seek to explain this gap, looking at the context of conflict both prior to and after the decision of establishing FeFo.